Blockade of TNFR2 signaling enhances the immunotherapeutic effect of CpG ODN in a mouse model of colon cancer - Nie, Yingjie (Sci Signal, 2018)
Through the tumor necrosis factor (TNF) receptor type II (TNFR2), TNF preferentially activates, expands, and promotes the phenotypic stability of CD4(+)Foxp3(+) regulatory T (Treg) cells. Those Treg cells that have a high abundance of TNFR2 have the maximal immunosuppressive capacity. We investigated whether targeting TNFR2 could effectively suppress the activity of Treg cells and consequently enhance the efficacy of cancer immunotherapy. We found that, relative to a suboptimal dose of the immunostimulatory Toll-like receptor 9 ligand CpG oligodeoxynucleotide (ODN), the combination of the suboptimal dose of CpG ODN with the TNFR2-blocking antibody M861 more markedly inhibited the growth of subcutaneously grafted mouse CT26 colon tumor cells. This resulted in markedly fewer TNFR2(+) T(reg) cells and more interferon-γ–positive (IFN-γ(+)) CD8(+) cytotoxic T lymphocytes infiltrating the tumor and improved long-term tumor-free survival in the mouse cohort. Tumor-free mice were resistant to rechallenge by the same but not unrelated (4T1 breast cancer) cells. Treatment with the combination of TNFR2-blocking antibody and a CD25-targeted antibody also resulted in enhanced inhibition of tumor growth in a syngeneic 4T1 mouse model of breast cancer. Thus, the combination of a TNFR2 inhibitor and an immunotherapeutic stimulant may represent a more effective treatment strategy for various cancers.